ESFERAS CONSTITUCIONALES TÍPICAS DE INTERACCIÓN ENTRE LAS CÁMARAS DEL PARLAMENTO EN LOS PAÍSES DE ASIA (Revista Inclusiones, 2018)
This study was aimed to investigate and analyze the constitutional texts of Asian states with a bicameral parliament in order to consolidate the typical areas of interaction among the chambers of parliaments. The results of analysis in present study showed that typical areas of interaction among chambers of parliament and international sphere providing the interaction among chambers with respect to foreign policy. It was concluded that the typical areas of interaction among chambers of parliaments in Asian countries reflect established approaches to the constitution of their statuses.